Components and services for IoT platforms : paving the way for IoT standards - Keramidas, Georgios; Voros, Nikolaos S.; Hübner, Michael, 1970- (Springer, 2016)
This book serves as a single-source reference to the state-of-the-art in Internet of Things (IoT) platforms, services, tools, programming languages, and applications. In particular, the authors focus on IoT-related requirements such as low-power, time-to-market, connectivity, reliability, interoperability, security, and privacy. Authors discuss the question of whether we need new IoT standardization bodies or initiatives, toward a fully connected, cyber-physical world. Coverage includes the research outcomes of several, current European projects related to IoT platforms, services, APIs, tools, and applications. Provides readers with a single-source reference to the state-of-the-art in Internet of Things (IoT) platforms, services, tools, programming languages, and applications; Includes research outcomes of several, current European projects on IoT-related requirements such as low-power, reliability, interoperability, security, and privacy; Enables a multi-disciplinary audience to understand the primitives for designing the next generation of cyber-physical systems and associated devices.
Includes index.
Keywords: Internet of things.; Cloud computing.; elektronické knihy; electronic books